Trends and factors for dropout among secondary school students in Perak - Mokshein, Siti Eshah; Wong, Kung Teck; Ibrahim, Haniz (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
The study sought to investigate the dropout trends and patterns among the secondary school students by district in Perak. The study employed a combination of quantitative and qualitative methods involving cohort flow analysis of student enrolment, interviews and document analysis. In the first part, student enrolment by grade level in 2000-2010 in all the nine districts in Perak from the database provided by the Ministry of Education was analyzed. In the second part, data were gathered through interviews from Batang Padang District that demonstrated highest dropout rate so as to further understand why secondary school students dropped out from schools, what are those students doing after leaving schools and explore their views on what could have been done to keep them in schools. Results showed that average of total loss between Form 1 and Form 5 in Perak State was 8.11 percent. The highest percentage of dropout was in Batang Padang (16.52%), followed by Manjung (11.9%), Hilir Perak (11.06%) and Kinta District (10.87%). Major factors of dropout were poor academic achievement, lack of interest in schooling, and influence from non-schooling siblings and home environmental factors. Majority of the students were still staying with their parents with a few of them doing part-time jobs or helping out their parents while many just stayed at home or hanged out with friends. Some policy implications and recommendations were also discussed in the paper.